2015
DOI: 10.1159/000441215
|View full text |Cite
|
Sign up to set email alerts
|

Sound Classification and Call Discrimination Are Decoded in Order as Revealed by Event-Related Potential Components in Frogs

Abstract: Species that use communication sounds to coordinate social and reproductive behavior must be able to distinguish vocalizations from nonvocal sounds as well as to identify individual vocalization types. In this study we sought to identify the neural localization of the processes involved and the temporal order in which they occur in an anuran species, the music frog Babina daunchina. To do this we measured telencephalic and mesencephalic event-related potentials (ERPs) elicited by synthesized white noise (WN), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 85 publications
(92 reference statements)
7
30
0
Order By: Relevance
“…In particular, the strengths of GC causal brain network connections in music frogs within the time window of the N1, P2 and P3 ERP components varied with the acoustic stimulus type and were sexually dimorphic. The results of the present study also show that the factor 'reproductive status' has neither main effects nor interactions with other factors, consistent with previous studies revealing that reproductive status does not affect the amplitude and latency of auditory ERP components elicited by male advertisement calls and white noise (Fang et al, 2015). The GC connections therefore represent relatively stable network properties not readily susceptible to seasonal hormonal influences.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In particular, the strengths of GC causal brain network connections in music frogs within the time window of the N1, P2 and P3 ERP components varied with the acoustic stimulus type and were sexually dimorphic. The results of the present study also show that the factor 'reproductive status' has neither main effects nor interactions with other factors, consistent with previous studies revealing that reproductive status does not affect the amplitude and latency of auditory ERP components elicited by male advertisement calls and white noise (Fang et al, 2015). The GC connections therefore represent relatively stable network properties not readily susceptible to seasonal hormonal influences.…”
Section: Discussionsupporting
confidence: 91%
“…Electrophysiological studies have shown that call playback stimuli elicit N1 ERP components significantly different from those elicited by white noise (WN) (Fang et al, 2015), consistent with the idea that music frogs allocate attention on the basis of the biological significance of sounds insofar as N1 is not solely determined by sensory processing but is modulated by attention (Gazzaniga et al, 2014). Moreover, both resting-state brain networks (Xue et al, 2016b) and functional brain networks associated with auditory perception (Xue et al, 2016a) have been identified in the music frog, suggesting that brain functions such as attention are mediated by specific brain networks.…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations